Epigenetic Regulation of Intronic Transgenes in Arabidopsis - Osabe, Kenji (Sci Rep, 2017)
Defense mechanisms of plant genomes can epigenetically inactivate repetitive sequences and exogenous transgenes. Loss of mutant phenotypes in intronic T-DNA insertion lines by interaction with another T-DNA locus, termed T-DNA suppression, has been observed in Arabidopsis thaliana, although the molecular basis of establishment and maintenance of T-DNA suppression is poorly understood. Here we show that maintenance of T-DNA suppression requires heterochromatinisation of T-DNA sequences and the nuclear proteins, INCREASED IN BONSAI METHYLATION 2 (IBM2) and ENHANCED DOWNY MILDEW 2 (EDM2), which prevent ectopic 3′ end processing of mRNA in atypically long introns containing T-DNA sequences. Initiation of T-DNA suppression is mediated by the canonical RdDM pathway after hybridisation of two T-DNA strains, accompanied by DNA hypermethylation of T-DNA sequences in the F1 generation. Our results reveal the presence of a genome surveillance mechanism through genome hybridisation that masks repetitive DNAs intruding into transcription units.